Delirium Accompanied by Cholinergic Deficiency and Organ Failure in a 73-Year-Old Critically Ill Patient: Physostigmine as a Therapeutic Option - Benedikt Zujalovic; Eberhard Barth (Case Reports in Critical Care)
Delirium is a common problem in ICU patients, resulting in prolonged ICU stay and increased mortality. A cholinergic deficiency in the central nervous system is supposed to be a relevant pathophysiologic process in delirium. Acetylcholine is a major transmitter of the parasympathetic nervous system influencing several organs (e.g., heart and kidneys) and the inflammatory response too. This perception might explain that delirium is not an individual symptom, but rather a part of a symptom complex with various disorders of the whole organism. The cholinergic deficiency could not be quantified up to now. Using the possibility of bedside determination of the acetylcholinesterase activity (AChE activity), we assumed to objectify the cholinergic homeostasis within minutes. As reported here, the postoperative delirium was accompanied by a massive hemodynamic and renal deterioration of unclear genesis. We identified the altered AChE activity as a plausible pathophysiological mechanism. The pharmacological intervention with the indirect parasympathomimetic physostigmine led to a quick and lasting improvement of the patient’s cognitive, hemodynamic, and renal status. In summary, severe delirium is not always an attendant phenomenon of critical illness. It might be causal for multiple organ deterioration if it is based on cholinergic deficiency and has to be treated at his pathophysiological roots whenever possible.